Cerminan Interaksi Sosial dan Nilai Gotong Royong Masyarakat dalam Upacara Koda Getok di Desa Leworok - Kamelia Ongo Makin; Hiwa Wonda (STKIP Subang, 2025)
The Koda Geto ceremony is a sacred tradition of the Leworok Village community that holds significant social and cultural functions in maintaining communal harmony. Based on a literature review, Koda Geto is not only understood as a religious ritual but also as a reflection of social interaction and the deeply rooted value of mutual cooperation (gotong royong) within the community’s life. This study aims to describe and analyze the forms of social interaction and mutual cooperation values reflected in the implementation of the Koda Geto ceremony in Leworok Village. The research employs a qualitative descriptive method with a literature study approach, in which data were obtained from various journals, books, and relevant scientific sources. Data analysis was conducted through the stages of reduction, presentation, and conclusion drawing to gain a deep understanding of the socio-cultural meanings within the tradition. The findings show that Koda Geto plays an important role as a medium for strengthening solidarity, togetherness, and respect for ancestral values through the practice of community cooperation. This study recommends the preservation of Koda Geto through local cultural education and social activities to ensure that the values of unity and cooperation in the Leworok community remain intact amid modernization.